Improving safety and reducing error in endoscopy: simulation training in human factors. Issue 2 (9th January 2019) - Ravindran, Srivathsan; Thomas-Gibson, Siwan; Murray, Sam; Wood, Eleanor
Abstract : Patient safety incidents occur throughout healthcare and early reports have exposed how deficiencies in 'human factors' have contributed to mortality in endoscopy. Recognising this, in the UK, the Joint Advisory Group for Gastrointestinal Endoscopy have implemented a number of initiatives including the 'Improving Safety and Reducing Error in Endoscopy' (ISREE) strategy. Within this, simulation training in human factors and Endoscopic Non-Technical Skills (ENTS) is being developed. Across healthcare, simulation training has been shown to improve team skills and patient outcomes. Although the literature is sparse, integrated and in situ simulation modalities have shown promise in endoscopy. Outcomes demonstrate improved individual and team performance and development of skills that aid clinical practice. Additionally, the use of simulation training to detect latent errors in the working environment is of significant value in reducing error and preventing harm. Implementation of simulation training at local and regional levels can be successfully achieved with collaboration between organisational, educational and clinical leads. Nationally, simulation strategies are a key aspect of the ISREE strategy to improve ENTS training. These may include integration of simulation into current training or development of novel simulation-based curricula. However used, it is evident that simulation training is an important tool in developing safer endoscopy.